Efforts To Improve The Achievement Of Schools Through The Implementation Of Study Based Management In Smkn 3 Rejang Lebong - Suparman, Asep; Hadiwinarto, Hadiwinarto (Yayasan Darussalam Bengkulu, 2020)
The principal is the leader and manager in the school, managing the school in conditions of limited infrastructure and the majority of quadrant IV students require a lot of innovation that must be done. The purpose of writing this best practice is to present a description or description of innovations about improving limited school achievement and the majority of Quadran IV students through the application of prosi-based management. The formulation of the problem in writing this best practice: can the application of prosi-based school management improve school achievement in limited sarpras schools and the majority of quadran IV students? and what is the evidence that the application of prosi-based management can improve school achievement in limited sarpras schools and the majority of quadran IV students? The method used in writing this best practice is descriptive qualitative. The implementation of prosi-based school management began in mid-February 2014 until now. After the implementation of problematic-based school management and its solutions (prosi), every year school achievement has increased. Based on the results and discussion of best practices, the following conclusions can be drawn: (1) The implementation of prosi management in sarpras schools is limited and the majority of quadrant IV students at SMKN 3 Rejang Lebong Bengkulu Province have proven to be able to improve school achievement; (2) Evidence of the successful implementation of prosi-based management at SMKN 3 Rejang Lebong are: (1) in 2015 the school received an award from the Minister of Education and Culture regarding schools that have high integrity in organizing the National Examination; (2) in 2016 began to receive the appointment of LPMP Bengkulu to become a model school for the Internal Quality Assurance System (SPMI); in 2017 the school was still a SPMI model school and students won achievements in the O2SN and Vocational High School Student Competency Contest (LKS) at the Regency, Provincial and National Levels. In 2018, he won many achievements in the LKS SMK at the Bengkulu Province level including 1st place in Livestock and Fishery, 2nd place in Pharmacy and 3rd place in IT / Networking support. In 2018, the writer as the principal of the school received an award from the Minister of Education and Culture as the second winner of the Best Practice Competition for the National Level Vocational Principals. In 2019, students of SMKN 3 Rejang Lebong won 3rd place in the field of pencak silat in the National Vocational High School Student Sports Olympiad (O2SN). Another proof of the success of the application of prosi management is that many other schools have begun to arrive for comparative studies at SMKN 3 Rejang Lebong, such as: SMKN 2 Bengkulu Tengah and SMKN 2 Seluma. Then in 2019 SMKN 3 Rejang Lebong was designated as a reference school by the Directorate of Vocational Development of the Ministry of Education and Culture.